(untitled) (Bangladesh Journal of Medical Science, 2018)
Objective: This study aims to to investigate calcium metabolism indices and bone mineralization in patients with coronary heart disease complicated by stage II-A chronic heart failure. Materials and Methods: The study involved 33 men with coronary heart disease (CHD) complicated by Stage II-A chronic heart failure (according to the classification by N.D. Strazhesko, V.H. Vasilenko and G.F. Lung (1935). Bone mineral density was measured using dual energy x-ray densitometry of lumbar region of spine. The level of 25-hydroxyvitamin D (25(ОН)D) has been detected by ELISA method using commercial Vitamin D3 screening kit (Switzerland). The level of ionized calcium was measuring by ion selective method using analyser of electrolytes AEK-01 (QuertiMed, Ukraine). Results and Discussion: Structural and functional changes of bone tissue of the lumbar spine have been found in 49,2 percent patients with coronary heart disease complicated by Stage II-A chronic heart failure, in particular, I stage of osteopenia – in 44,6 %, II stage of osteopenia – in 27,7 %, III stage of osteopenia – in 10,8 % and osteoporosis – in 16,9 %. It was established the same type of downward trend for BMD decreasing in L1 of patients with different stages of osteopenia, but in case of osteoporosis mineralization decreased equally in all vertebrae. The analysis of calcium metabolism indices indicate that concentration of ionized calcium significantly decreased in patients with CHD complicated by Stage II-A chronic heart failure vs control (1.26±0.02 mmol/l) by 11.1 % (I stage of osteopenia), 18.3 % (II stage of osteopenia) and 31.7 % (III stage of osteopenia). Similar tendency was observed towards concentration of 25(ОН)D. Conclusion: In patients with CHD complicated by Stage II-A chronic heart failure we have established statistically significant decrease in serum level of ionized calcium and 25-hydroxyvitamin D concentration. However, we didn’t find the relationship between serum calcium, 25-hydroxyvitamin D concentration and bone mineral density. Structural and functional changes of bone tissue of the lumbar spine have been found in 49,2 percent patients with coronary heart disease complicated by Stage II-A chronic heart failure. It was established the same type of downward trend for BMD decreasing in L1 of patients with different stages of osteopenia, but in case of osteoporosis mineralization decreased equally in all vertebrae. Bangladesh Journal of Medical Science Vol.17(3) 2018 p.395-401